THU0019 Association of HLA-B*41:02 with Henoch-Schönlein Purpura in Spanish Individuals Irrespective of the HLA-DRB1 Status. (9th June 2015) - Lόpez-Mejías, R.; Genre, F.; Sevilla Pérez, B.; Castañeda, S.; Ortego-Centeno, N.; Llorca, J.; Ubilla, B.; Remuzgo-Martínez, S.; Mijares, V.; Pina, T.; Calvo-Río, V.; Márquez, A.; et al.
Abstract : Background: To determine whether the human leukocyte antigen ( HLA ) B alleles are implicated in the susceptibility to Henoch-Schönlein purpura (HSP) in the largest series of Caucasian HSP patients ever assessed for genetic studies. Methods: The study population was composed of 349 Spanish patients diagnosed with HSP fulfilling the American College of Rheumatology and the Michel et al. classification criteria, and 335 sex and ethnically matched controls. HLA-B phenotypes were determined by sequencing-based typing (SBT) and analyzed by chi-square or Fisher exact test. Results: A statistically significant increase of HLA-B*41:02 allele in HSP patients when compared with controls was found (8.3% versus 1.5% respectively; p=0.0001; OR (odds ratio) =5.76 [2.15-19.3]). These results remained statistically significant after adjusting for Bonferroni correction (p=0.0028). An internal validation also confirmed the susceptibility effect on HSP associated with HLA-B*41:02 (OR=5.70 [1.98-16.44]). Since a former study described an association between HLA-DRB1*01:03 and HSP susceptibility, we also evaluated the implication of HLA-B*41:02 independently of HLA-DRB1*01:03 . Interestingly, the association remained statistically significant (p=0.0004, OR=4.97 [1.8-16.9]). No HLA-B association with specific HSP clinical features was found. Conclusions: Our study indicates that HLA-B*41:02 is associated with the susceptibility to HSP in Spanish patients irrespective of HLA-DRB1 status. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). RLM is a recipient of a Sara Borrell postdoctoral fellowship from the Instituto de Salud Carlos III at the Spanish Ministry of Health (Spain) (CD12/00425). FG and BU are supported by funds from the RETICS Program (RIER) (RD12/0009/0013). Disclosure of Interest: None declared